CITRA PEREMPUAN DALAM NOVEL NAYLA KARYA DJENAR MAESA AYU DAN NOVEL TUHAN, IZINKAN AKU MENJADI PELACUR KARYA MUHIDIN M. DAHLAN (SEBUAH KAJIAN KRITIK FEMINISME) - Maria Ulviani (JURNAL KONFIKS, 2018)
Based on data analysis, it is concluded that in Nayla, Djenar Mahesa Ayu shows the women’s images in the story. This is proved by critical mapping regarding the focus of the study which is physical images through the character of lead figure in the novel. Therefore it is inferred that Nayla as the main character is affected and dominated by psychological problems that are immersed becoming her character. Attitude and self-consistency are also described as the value of Nayla’s character. Besides, based on feminism analysis identified from Tuhan, Izinkan Aku Menjadi Pelacur (God, Let Me become A Prostitute) by Muhidin M. Dahlan, it is concluded that weak women tend to get the kind of abuses from men. Women who easily get doctrine with fraud pledges will turn to be more hurt and disappoint with their life and reality. Additionally, the disappointments to other people can also turn women to the disappointment to God.